Stokesay Castle
The lower end of Stokesay is crowned by this fine solar, built over the fortified wall during the seventeenth century, which also saw the building of the half-timbered gatehouse. Both indicate the future trend toward domestic architecture. In the coming years it was to be the turn of the gentleman and merchant. Survivors of the twin catastrophes of plague and civil war, they went on to build internationally powerful society whose outposts bordered America and India in place of Wales, while Church and State, content to let them do the work, stood by.